Budaya Disiplin Cuci Tangan Pakai Sabun (CTPS) Siswa Sekolah Dasar di Masa Endemi Covid-19: Literature Review - Sevtivia Asrivi, Queen Elvina; Maulida Asaroh, Eva (Tunas Nusantara, 2025)
The Corona Virus Disease 2019 (COVID-19) outbreak has hit the world and changed the order of human life. Especially the education sector has an impact on the disruption of the teaching and learning process. Washing Hands with Soap (CTPS) which was previously considered unimportant has become a mandatory habit in activities for a period of -/+ 3 years. The CTPS habit has become a daily culture, however, after the enactment of Presidential Decree of the Republic of Indonesia Number 17 of 2023 concerning the change in the status of the COVID-19 pandemic to endemic, it has become a breath of fresh air for the community, especially elementary school students in carrying out learning. This study uses a qualitative library research approach. Literature research is used to critically and in-depth review of library materials that are relevant to the material. In this case, the analysis of journals published from 2020 to 2024 related to handwashing activities in elementary school students during the COVID-19 endemic. Several journal literatures related to the discussion material then analyze the material through literature studies with descriptive analysis results. The findings in this study are that the COVID-19 endemic causes elementary school students to experience resilience in the form of CTPS behavioral adaptation. Behavioral adaptation in the form of hand washing behavior before and after eating, defecating and urinating, etc. This resilience is influenced by the role model of teachers in the school environment and parents in the home environment. Supervision and guidance are still carried out so that students always remember to maintain their health through preventive steps of washing their hands. The teacher's actions become a figure for students in behaving every day. Students normalize what teachers do at school. This has an impact on student discipline in maintaining their health. Students need guidance and supervision related to health education as a preventive effort to protect themselves and others